PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI ELEKTROKIMIA - Fathimatuz Zahroh (Phenomenon : Jurnal Pendidikan MIPA, 2020)
Project Based Learning is a learning model that need collaboration from group member in each stage, so that students can develop their critical thinking skills. The aim of this study is to determine the effect of PjBL to students’ critical thinking skills on electrochemistry material.  The research design used true experimental design with pretest-posttest control group design and sampling technique is cluster random sampling. The data collection techniques used pretest-posttest to understand 10 critical thinking indicators, observation sheet used to understand students’ project activities and questionnaire to know students’s responses. Data Analysis techniques that used in this study are average difference test, significant test, product moment correlation test, coefficient of determination test. Analysis of product moment correlation value is 0,67 for students’ critical thinking skill with significant test result is 7,10 indicate the significant effect of PjBL to students’ critical thingking skills on electrochemistry material. The effect of PjBL to students’ critical thinking skills pointed by coefficient of determination  44,89%. Based on the results of the study, it was conclude that PjBL had positive effects on students’ critical thinking skills on electrochemistry material.